2016
DOI: 10.1002/path.4749
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary fibrosis fibroblasts become resistant to Fas ligand‐dependent apoptosis via the alteration of decoy receptor 3

Abstract: Idiopathic pulmonary fibrosis (IPF) is an irreversible lethal lung disease with an unknown aetiology. IPF patient’s lung fibroblasts express inappropriately high Akt activity, protecting them in response to an apoptosis-inducing type I collagen matrix. FasL, a ligand for Fas, is known to be increased in the lung tissues of patients with IPF, implicated with the progression of IPF. Expression of Decoy Receptor3 (DcR3) which binds to FasL, thereby subsequently suppressing the FasL/Fas-dependent apoptotic pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Our prior studies demonstrated that abnormally low FoxO3a protects IPF fibroblasts from collagen-rich matrix-driven apoptosis 9 , 10 , 32 . In this study, we elucidated that FoxO3a alteration directly contributes to reduced DNA damage via the FoxM1/RAD51–BRCA2-dependent axis, fortifying the crucial role of FoxO3a in IPF fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our prior studies demonstrated that abnormally low FoxO3a protects IPF fibroblasts from collagen-rich matrix-driven apoptosis 9 , 10 , 32 . In this study, we elucidated that FoxO3a alteration directly contributes to reduced DNA damage via the FoxM1/RAD51–BRCA2-dependent axis, fortifying the crucial role of FoxO3a in IPF fibroblasts.…”
Section: Discussionmentioning
confidence: 96%
“…Our data also support that radiation preferentially damages normal lung epithelial cells and fibroblasts, whereas resident pathological pro-fibrotic fibroblasts, which may be inhabitant in small numbers, are likely to survive and contribute to the fibrotic process. Fibrosis-inducing cells such as IPF fibroblasts flourish in collagen-rich conditions 9 , 10 , 32 , therefore the normal healing process following radiation injury may provide an environment that favors fibrosis. It is feasible that the presence of even a small population of pro-fibrotic lung fibroblasts in cancer patients may be at an increased risk of RILF following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of mechanisms involving inhibitor of apoptosis family proteins, BCL-2 family proteins, pro-survival protein kinase activation and cell-matrix interactions have been shown to regulate fibroblast susceptibility to apoptosis and accumulating studies demonstrate the feasibility of targeting fibroblast survival as a treatment strategy for fibrotic disease in the lung [ 1 , 4 , 21 , 24 , 36 , 37 ]. Additionally, several studies now indicate that regulation of Fas itself may contribute to fibroblast acquisition of an apoptosis-resistant phenotype, although our understanding of the underlying mechanisms continues to evolve [ 7 , 16 , 20 , 38 ]. In the current study, we have shown that pro-fibrotic soluble and mechanical stimuli suppress fibroblast expression of Fas through both transcriptional and post-transcriptional mechanisms, that decreased Fas correlates with resistance to apoptosis, and that enhanced apoptosis susceptibility in response to inflammatory cytokines is not diminished by TGF-β1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the death receptor-regulated membrane receptor apoptosis pathway. In this pathway, Caspase 8 is activated by Fas and its ligand FasL, and then it activates the membrane receptor apoptosis pathway [ 24 ]. The second is mitochondria apoptosis pathway.…”
Section: Discussionmentioning
confidence: 99%